2004
DOI: 10.1080/09670260410001710123
|View full text |Cite
|
Sign up to set email alerts
|

Large subunit rDNA gene sequences and reproductive morphology revealStenopeltisto be a member of the Liagoraceae (Nemaliales, Rhodophyta), with a description ofAkalaphycusgen. nov.

Abstract: A morphological and gene sequence study has shown the red algal genus Stenopeltis to be a member of the Liagoraceae (Nemaliales), not the Polyidaceae (Gigartinales) where it was placed after being segregated from Rhodopeltis. Post-fertilization events in Stenopeltis gracilis (the type of the genus) include a spreading, diffuse gonimoblast arising directly from the zygote ( = post-fertilization carpogonium), and no auxiliary cells, features characteristic of the Liagoraceae. Moreover, phylogenetic analyses base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…Chaetangiaceae was elevated to ordinal status by Desikachary (1964), but this has largely been ignored. Monophyly of the order has been demonstrated by Huisman et al (2004a,b) based on large-subunit ribosomal DNA sequences, and Huisman et al (2004a) also added a third family, the Scinaiaceae. However, relationships among genera in the family Liagoraceae sensu lato have remained mostly unexplored (Le Gall andSaunders 2010, Lin et al 2011a,b).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Chaetangiaceae was elevated to ordinal status by Desikachary (1964), but this has largely been ignored. Monophyly of the order has been demonstrated by Huisman et al (2004a,b) based on large-subunit ribosomal DNA sequences, and Huisman et al (2004a) also added a third family, the Scinaiaceae. However, relationships among genera in the family Liagoraceae sensu lato have remained mostly unexplored (Le Gall andSaunders 2010, Lin et al 2011a,b).…”
Section: Discussionmentioning
confidence: 91%
“…Monophyly of the order has been demonstrated by Huisman et al. (,b) based on large‐subunit ribosomal DNA sequences, and Huisman et al. () also added a third family, the Scinaiaceae.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To the best of our knowledge A. efflorescens had not been subjected to molecular analysis. We therefore sequenced nuclear large subunit ribosomal DNA (LSU), a region demonstrated to be taxonomically informative in the red algae at the ordinal level and below (Freshwater et al, 1999;Harper & Saunders, 2002;Huisman et al, 2004;Saunders & Lehmkul, 2005), to assess its molecular relationship to other acrochaetioid algae. …”
Section: Introductionmentioning
confidence: 99%
“…The only study to date of Hawaiian stream macroalgae including molecular data is a phenologic and phylogenetic study of the endemic red alga Batrachospermum spermatiophorum ), which confirmed the endemic status of the species by comparison of rbcL gene sequence data with worldwide congeners. The Hawaiian representatives of the marine red algal order Nemaliales have recently undergone substantial revision based on combinations of anatomical and molecular data (e.g., Huisman et al 2003Huisman et al , 2004a, and many changes may also be forthcoming for the freshwater flora following similar kinds of studies. Specifically, several potentially undescribed taxa were collected during the survey reported here (e.g., two Phormidium taxa and two Cladophora taxa).…”
Section: Floristic Analyses Of Hawaiian Stream Macroalgaementioning
confidence: 99%